Enhancing Chemistry Education for Students through a Novel Card Game: Compound Chain - Tursyngozhayev, Kaisar; Kavak, Nusret; Akhmetov, Nurlan K. (Journal of chemical education, 2024)
The teaching and learning of chemistry can be challenging due to the complex and abstract nature of the subject matter. Traditional methods of instruction often struggle to engage students and facilitate an understanding of essential chemical concepts. To address this, an innovative card game, “Compound Chain”, was developed and introduced to chemistry classes in middle school. “Compound Chain” is a color and compound matching game inspired by popular shedding-type card games, but with a significant twist: the colors and numbers are replaced by different types of inorganic compounds and their properties, thus turning gameplay into a dynamic and engaging learning process. It incorporates various aspects of inorganic chemistry, such as compound types, oxidation states, solubility, conductivity, and relationships between elements and their compounds. The aim of this study was to evaluate the effectiveness of “Compound Chain” as an educational tool for improving the understanding of chemistry concepts and increasing the level of engagement among students. The research utilized a pretest–posttest design, with the participants’ performance and engagement being assessed before and after the implementation of “Compound Chain” in their chemistry curriculum. The results indicate a significant increase in students’ comprehension, problem-solving abilities, and enjoyment of the subject. Furthermore, students reported a greater appreciation for the interconnectedness of the chemical concepts. These findings demonstrate the potential of “Compound Chain” as an innovative and interactive educational tool that can supplement traditional chemistry instruction and foster a deeper understanding of the subject matter, improving students’ performance and engagement in the classroom.